Transcranial electric stimulation optimizes the balance of visual attention across space. Issue 4 (April 2020) - Andres, Michael; Masson, Nicolas; Larigaldie, Nathanael; Bonato, Mario; Vandermeeren, Yves; Dormal, Valérie
Highlights: The study tested the potential benefit of bilateral transcranial direct current stimulation (tDCS) for attention modulation. Left anodal and right cathodal tDCS increased visual sensitivity in both fields. TDCS may boost attention resources and facilitate functional rehabilitation. Abstract: Objective: Transcranial direct current stimulation (tDCS) provides a way to modulate spatial attention by enhancing the ratio of neural activity between the left and right hemispheres, with a potential benefit for the rehabilitation of visual neglect. Methods: We tested the effect of bilateral tDCS in healthy individuals performing a visual detection task. This protocol consists in the positioning of the anode and cathode on mirror positions over the left and right parietal areas. The stimulation was repeated over three days to maximize the chance to observe a bias to the hemispace controlateral to the anode. Results: Compared to a sham treatment, left anodal – right cathodal stimulation enhanced attention across the full range of space, since the first day with no build-up effect on the next days, and modified the balance of left-right omissions when stimuli appeared at the same time. Conclusion: Bilateral tDCS improved detection in both visual fields, with no privileged processing of one side, except when concurrent stimuli were presented. The results provide partial support to the hemispheric rivalry hypothesis. Significance: The technique has the potential to boost attention in neglect patients but should be used as an adjuvant rather than as an alternative to functional rehabilitation.